The Development of Analytical Thinking Skill by Using Technique 5W1H with YouTube on Al-Akhlaq Subject for Primary School Students, Year 3 - Maming, Fateehah; Haengyama, Muhamadsuhaimi; Suwanno, Phimpawee; Nesalaeh, Muhammad (MENARA : Journal of Islamic and Contemporary Issues, 2024)
The objectives of this research were 1) to develop and find out the effectiveness of learning plans towards analytical thinking skill by using 5W1H teaching technique with YouTube on al-Akhlaq subject for primary school students, year 3. 2) to compare analytical thinking skill between before and after learning using 5W1H teaching technique with YouTube. 3) to compare the students achievement on al-Akhlaq subject between before and after learning. 4) to assess students satisfaction on al-Akhlaq subject using 5W1H teaching technique with YouTube. The target population used in this research was primary school students, year 3 at Ban Sakho School in semester 2 of academic year 2022, in total of 9 students. Tools used in the experiment: 1) The learning management plans on al-Akhlaq subject according to develop analytical thinking skill by using the 5W1H teaching technique with YouTube media. 2) Using 5W1H Teaching technique with YouTube; 3) Learning achievement test on al-Akhlaq subject; 4) Students satisfaction questionnaire on learning management using 5W1H teaching technique with YouTube. The research statistics used were percentage, mean, standard deviation and Statistics used for testing is Wilcoxon signed ranks test. The results of the research found that; 1) The effectiveness of the learning management plans to develop analytical thinking skill by using 5W1H teaching technique with YouTube on al-Akhlaq subject for primary school students, year 3 has an efficiency of 81.74/87.04 2) The analytical thinking skill between, before and after learning on al-Akhlaq subject for primary school students, year 3 after learning was statistically significantly higher than before learning at level 0.05 3) The learning achievement on al-Akhlaq subject between before and after learning al-Akhlaq subject primary school students, year 3 after learning was statistically significantly higher than before learning at level 0.05 and 4) Students satisfaction of learning management on al-Akhlaq subject by using 5W1H teaching technique with YouTube was at the high level